Percutaneous embolization of congenital portosystemic venous shunt in an infant with respiratory distress - Alkan, Fatoş; Düzgün, Fatih; Yüksel, Hasan; Tarhan, Serdar; Coşkun, Şenol (The Turkish Journal of Pediatrics, 2018)
A 5-month-old boy with progressive respiratory distress was admitted to our hospital. Physical examination revealed mild tachypnea and retraction. The left main bronchus was found as severely collapsed between the right pulmonary artery and the descending aorta, on the bronchoscopic evaluation. Further evaluation revealed persistent ductus venosus (PDV). As in the fetal period the ductus venosus arises from the posterior aspect of the left portal vein, a PDV is considered another type of intrahepatic portosystemic shunt. Therefore, he was diagnosed with congenital portosystemic venous shunt, leading to persistent respiratory distress. The PDV was closed with Amplatzer vascular plug II, and then he had immediate clinical improvement. Congenital portosystemic venous shunts (CPSS) are rare vascular malformations associated with severe complications. Here we presented a case with progressive respiratory distress as a result of CPSS and rapid improvement after embolization.
Keywords: amplatzer vascular plug II.; persistent ductus venosus; portosystemic venous shunt